Marine Bacterial Sialyltransferases - Takeshi Yamamoto (Marine Drugs, 2010)
Sialyltransferases transfer N-acetylneuraminic acid (Neu5Ac) from the common donor substrate of these enzymes, cytidine 5’-monophospho-N-acetylneuraminic acid (CMP-Neu5Ac), to acceptor substrates. The enzymatic reaction products including sialyl‑glycoproteins, sialyl-glycolipids and sialyl-oligosaccharides are important molecules in various biological and physiological processes, such as cell-cell recognition, cancer metastasis, and virus infection. Thus, sialyltransferases are thought to be important enzymes in the field of glycobiology. To date, many sialyltransferases and the genes encoding them have been obtained from various sources including mammalian, bacterial and viral sources. During the course of our research, we have detected over 20 bacteria that produce sialyltransferases. Many of the bacteria we isolated from marine environments are classified in the genus Photobacterium or the closely related genus Vibrio. The paper reviews the sialyltransferases obtained mainly from marine bacteria.